The fear of spiders: perceptual features assessed in augmented reality - Frumento, Sergio; Frumento, Paolo; Laurino, Marco; Menicucci, Danilo; Gemignani, Angelo (Frontiers in Behavioral Neuroscience, 2024)
Persons with specific phobias typically generalize the dangerousness of the phobic animal to all members of its species, possibly as a result of a malfunctioning brain circuitry normally providing quick-and-dirt identification of evolutionary-relevant stimuli. An objective assessment of which perceptual features make an animal more-or-less scary to phobic and non-phobic people would overcome the limitations of the few studies available so far, based on self-reports.To this aim, we built an augmented-reality setting where volunteers with different levels of fear for spiders were asked to make holographic spiders look like dangerous or harmless. To reach this goal, a computerized interface allowe participants to modify spider's perceptual features (hairiness, body/leg size and locomotion) in real time.On average, the dangerous spiders were made hairy, thick, and moving according to a spiderlike locomotion; coherently, the harmless spiders were made hairless, slim, and moving according to a butterfly-like locomotion. However, these averaged preferences could not fully describe the complex relationship between perceptual preferences with each other and with arachnophobic symptoms: an example of a key finding revealed by cluster analysis consists in the similarity in perceptual preferences among participants with little or null fear for spiders, whereas participants with more arachnophobic symptoms expressed more varying preferences.Perceptual preferences toward spider's features were behaviorally assessed through an observational study, objectively confirming a generalization effect characterizing spider-fearful participants These results advance our knowledge of phobic preferences and could be used to improve acceptability of exposure therapies.